EFFECTIVENESS AIS ON USER SATISFACTION, REAL TIME REPORTING TO THE ORGANIZATIONAL IMPACT - Candra Devi, Meita; Kartika Pratiwi Putri; Dodi Tisna Amijaya; Hendri Maulana (Dinasti Publisher, 2020)
Accounting Information System (AIS) is an important factor in increasing employee satisfaction and reporting company performance in real time. Research to find out the effectiveness of the adoption of AIS for user satisfaction and real-time reporting and to see the impact of the organization is done by the survey method. The number of respondent's National Private Commercial Banks was 45 from 65 population. Data collection was carried out by distributing questionnaires, and then analyzed using PLS (Partial Least Square). The results show that as partially the effectiveness applying AIS has a positive effect on user satisfaction of 28,353, real-time reporting and organizational impact. Partial user satisfaction and real-time reporting also have a positive effect on organizational impact. Simultaneously the effectiveness of implementing an AIS, user satisfaction and real time reporting also have a positive effect on the organization's impact. This finding reveals that AIS could increase the organization impact.